Implementation of Kalman filter for the indoor location system of a Lego NXT mobile robot - López Osorio, Leidy; Bermúdez Bohórquez, Giovanni; Pérez Pereira, Miguel (Visión electrónica, 2014)
This paper shows the implementation of an estimation technique based on Kalman filter to correct accumulated errors that occur along a trajectory when tracking location over a mobile platform (Lego NXT 2.0 type) in a known environment. The implementation begins with kinematic models and odometers to subsequently construct the filter and conduct the corresponding experimentation.